Is distance dying at last? Falling home bias in fixed effects models of patent citations - Rachel Griffith; Sokbae Lee; John Van Reenen (Centre for Microdata Methods and Practice (cemmap), 2011)
We examine the home bias of knowledge spillovers (the idea that knowledge spreads more slowly over international boundaries than within them) as measured by the speed of patent citations. We present econometric evidence that the geographical localization of knowledge spillovers has fallen over time, as we would expect from the dramatic fall in communication and travel costs. Our proposed estimator controls for correlated fixed effects and censoring in duration models and we apply it to data on over two million patent citations between 1975 and 1999. Home bias is exaggerated in models that do not control for fixed effects. The fall in home bias over time is weaker for the pharmaceuticals and information/communication technology sectors where agglomeration externalities may remain strong.
Keywords: O32; O33; F23; 330; fixed effects; home bias; patent citations; knowledge spillovers; Wissenstransfer; Bibliometrie; Patent; Home Bias Puzzle; Informationskosten; OECD-Staaten